2011
DOI: 10.1074/jbc.m111.248765
|View full text |Cite
|
Sign up to set email alerts
|

Dimer Interface of the Effector Domain of Non-structural Protein 1 from Influenza A Virus

Abstract: Influenza is a contagious respiratory illness in humans caused by influenza A and B viruses that results in an annual average of 36,000 deaths in the United States alone (www.cdc. gov/Flu). Influenza A viruses, infecting birds and mammals, periodically cause widespread pandemics, the most deadly of which was the 1918 "Spanish Flu" pandemic that claimed an estimated 50 million lives (1). In recent years, the appearance of new H5N1 and H1N1 influenza A viruses, known as "avian flu" and "swine flu," respectively,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

12
117
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(129 citation statements)
references
References 58 publications
12
117
0
Order By: Relevance
“…Here, we used the mouse-lethal A/Puerto Rico 8/34 (PR8) strain both to allow in vivo experiments and to negate the impact of mutation of W187 on the cellular pre-mRNA processing inhibition ability of NS1, which is inherently lacking in the NS1 of PR8 and many other strains (11,13,21). Consistent with previous studies implicating the NS1 ED helix-helix dimer in RBD function (1,12), poly(I·C) pulldown assays confirmed that the W187R mutation reduces dsRNA binding by NS1 (Fig. 1C).…”
supporting
confidence: 57%
See 4 more Smart Citations
“…Here, we used the mouse-lethal A/Puerto Rico 8/34 (PR8) strain both to allow in vivo experiments and to negate the impact of mutation of W187 on the cellular pre-mRNA processing inhibition ability of NS1, which is inherently lacking in the NS1 of PR8 and many other strains (11,13,21). Consistent with previous studies implicating the NS1 ED helix-helix dimer in RBD function (1,12), poly(I·C) pulldown assays confirmed that the W187R mutation reduces dsRNA binding by NS1 (Fig. 1C).…”
supporting
confidence: 57%
“…As controls, wild-type (WT) NS1 bound efficiently to poly(I·C), while no binding was observed for the dsRNA-binding-incompetent R38A mutant (12,22). Although we noted that the effect of W187R on poly(I·C) binding was not as striking as that of a previously reported mutation (W187A) ((12; data not shown), our observation confirms that ED dimerization contributes to the overall affinity of full-length NS1 for dsRNA, which probably only occurs efficiently via cooperative binding of NS1 multimers (1,3).…”
supporting
confidence: 48%
See 3 more Smart Citations